Computed Tomography (CT) contributes in the functional outcome of Endoscopic Septopasty - Islam MA; Mamoon TB; Miki FU; Chowdhury NH; Khan SR; Rahman ASL; Miah MAS; Mohammad T (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Background and objective: Septoplasty is the common surgical procedure performed in nasal septal deviation. Nasal obstruction is the most frequent presentation to the otolaryngologist all over the world with septal deviation. Patients usually presented with headache, epistaxis, ophthalmological, otological, upper and lower respiratory tract infections; and many more. Physical examination, Anterior Rhinoscopy (AR) and Nasal Endoscopy (NE) are considered the gold standard tools to detect septal deviation. Computed Tomography (CT) contributes in the evaluation of the nasal septum, anatomical variants and unveils the associated sinonasal diseases. This study aimed to assess the contribution of CT in endoscopic septoplasty for long term benefits to the patients.  Patients and methods: 188 patients of nasal septal deviation were selected from 2015 to 2019 in the Bangladesh Medical and Popular Medical College Specialized Hospital. Age ranged in between 10 year to 70 year of age. CT scanning in both coronal, axial and sagittal sections had been done in all patients after proper history taking, physical examination, anterior rhinoscopy and nasal endoscopy. Endoscopic septoplasty alone and/or other ancillary procedures were performed in all 188 patients under general anesthesia. Results: Among 188 patients, male was 126 (67%) and female was 62 (33%) with a ratio 2:1. Maximum 63 (34%) reported in 31 to 40 year and 54 (29%) was found in 21 to 31 year of age. Hypertrophied Inferior Turbinate (HIT) 74 (39%) and 54 (29%) concha bullosa (CB) were associated with 188 septal deviation. Associated pathologies like maxillary sinusitis 82 (44%) and maxillary antral cyst 78 (41%) were documented. Conclusion: CT scanning detects the abnormal anatomic variants and associated sinonasal pathologies along with nasal septal deviation. Endoscopic septoplasty, correction of the anatomical variants and complete surgical clearance of the sinonasal pathologies can give the patient a long term outcome.